2007
DOI: 10.1007/s11605-007-0165-4
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Mortality and Postoperative Complications After Gastrointestinal Surgery

Abstract: Premorbid factors, characteristics of the disease, the patients' preoperative condition, operative factors, and the surgeon's training are all associated with surgical outcome across different gastrointestinal operations and should be assessed when auditing surgical outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
72
4
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(86 citation statements)
references
References 28 publications
7
72
4
1
Order By: Relevance
“…Collagen constitutes approximately one -third of the total protein content of any organism and is the predominant structural protein of the aponeurosis, where it is organized in fibres, whose chemical-physical characteristics render them particularly resistant to traction. Within the abdominal wall, as in other tissue, damaged collagen fibers are repaired through a process of proliferation and remodelling [7]. The aim of MMP proteolytic activity is to permit the passage of macrophages and fibroblasts across hydrolysed collagen fibres, leading to tissue repair where necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Collagen constitutes approximately one -third of the total protein content of any organism and is the predominant structural protein of the aponeurosis, where it is organized in fibres, whose chemical-physical characteristics render them particularly resistant to traction. Within the abdominal wall, as in other tissue, damaged collagen fibers are repaired through a process of proliferation and remodelling [7]. The aim of MMP proteolytic activity is to permit the passage of macrophages and fibroblasts across hydrolysed collagen fibres, leading to tissue repair where necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the mortality and post-operative complications in a wide variety of surgical populations, [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] but in the majority of studies, observation time is short and appears to vary between in-hospital, 30-day, and 90-day mortality.…”
Section: Editorial Commentmentioning
confidence: 99%
“…Several studies [25][26][27] confirmed that certain complex interventions carry the risk of increased complication rates when carried out by a nonspecialized surgeon or, similarly important, in a nonspecialized institution. In some studies [28,29], elective patients operated on by nonspecialized surgeons had almost twice the risk of postoperative death in gastrointestinal surgery. On the contrary, higher hospital caseload is not significantly associated with better outcomes in emergency colectomy [30].…”
Section: Handoffsmentioning
confidence: 99%
“…Within almost every surgical specialty, it has been shown that training is associated with outcome [28] to some extent. The training of surgical residents is permanently changing with new techniques and political issues relevant to working hour restrictions.…”
Section: Training Of Surgical Residentsmentioning
confidence: 99%